Moisture, temperature and light modualte methane oxidation from dry riverbeds - A mesocosms experiment - Clara Mendoza-Lera; Jonas Löwer; Lorenzo Rovelli (PANGAEA, 2025)
In this study, under lab conditions (Jan-Apr 2022) in we examined how three key drivers of methane oxidation in soils also modulate methane oxidation (i.e. methanotrophy) in dry riverbed sediments: gravimetric water content (GWC, as proxy of moisture), temperature, and light quality and intensity. We measured potential methane oxidation rates (PMO) as proxy of methanotrophy across a gradient of GWC, temperature (10, 20 and 30C), and under different light conditions (green and growth light) from dry (8% GWC) and wet (100%GWC) sediments collected in early Spring 2022 in the Queich River in Offenbach an der Queich (Germany). We used incubation vials (125mL) with about 10 mL sediment and spiked it with 120uL of pure methane gas following Bodmer et al. (2020). Incubations lasted for a week (until methane concentrations were below detection limit) and we replicated each treatment level four times (except for 10C that had just three).